GROWTH REGULATORS AND MICROFERTILIZER ON POLEMONIUM CАERULEUM L. APPLICATION: EFFECTIVENESS FOR MEDICINAL RAW MATERIAL AND SEEDS YIELD INCREASING - Firdaus M. Hazieva; Irina N. Korotkikh; Nikita I. Kovalev; Svetlana I. Romashkina; Tat’yana Е. Samatadze (Siberian Journal of Life Sciences and Agriculture, 2022)
Introduction. The article presents the results of the use of growth regulators and micro-fertilizers on the medicinal culture namely Polemonium ceruleum L. according to the concept of exogenous bioregulation of growth processes, the productivity of raw materials and the content of biologically active substances in raw materials. Rhizomes with roots of this species (Rhizomata cum radicibus Polemonii) are included in the Russian State Pharmacopoeia 14th edition as an expectorant.